Rapid bacterial identification by direct PCR amplification of 16S rRNA genes using the MinION™ nanopore sequencer. Issue 3 (29th January 2019) - Kai, Shinichi; Matsuo, Yoshiyuki; Nakagawa, So; Kryukov, Kirill; Matsukawa, Shino; Tanaka, Hiromasa; Iwai, Teppei; Imanishi, Tadashi; Hirota, Kiichi
Abstract : Rapid identification of bacterial pathogens is crucial for appropriate and adequate antibiotic treatment, which significantly improves patient outcomes. 16S ribosomal RNA (rRNA) gene amplicon sequencing has proven to be a powerful strategy for diagnosing bacterial infections. We have recently established a sequencing method and bioinformatics pipeline for 16S rRNA gene analysis utilizing the Oxford Nanopore Technologies MinION™ sequencer. In combination with our taxonomy annotation analysis pipeline, the system enabled the molecular detection of bacterial DNA in a reasonable time frame for diagnostic purposes. However, purification of bacterial DNA from specimens remains a rate‐limiting step in the workflow. To further accelerate the process of sample preparation, we adopted a direct PCR strategy that amplifies 16S rRNA genes from bacterial cell suspensions without DNA purification. Our results indicate that differences in cell wall morphology significantly affect direct PCR efficiency and sequencing data. Notably, mechanical cell disruption preceding direct PCR was indispensable for obtaining an accurate representation of the specimen bacterial composition. Furthermore, 16S rRNA gene analysis of mock polymicrobial samples indicated that primer sequence optimization is required to avoid preferential detection of particular taxa and to cover a broad range of bacterial species. This study establishes a relatively simple workflow for rapid bacterial identification via MinION™ sequencing, which reduces the turnaround time from sample to result, and provides a reliable method that may be applicable to clinical settings. Abstract : Direct amplification of 16S ribosomal RNA genes combined with MinION™ sequencing provides an attractive option for rapid detection of bacteria. Mechanical cell disruption preceding direct PCR is indispensable for obtaining an accurate representation of the bacterial composition. Our simple workflow for rapid bacterial identification reduces the turnaround time from sample to result and provides a reliable method applicable to clinical settings.